Cardiovascular Health Status in US Adults With Chronic Diseases: National Health and Nutrition Examination Survey (NHANES), 2013–2018 - James W. Guo; Hongyan Ning; Donald M. Lloyd‐Jones (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Cardiovascular health (CVH) assessment may have important benefits for adults with chronic diseases to prevent incident cardiovascular disease and additional chronic conditions. Few studies have compared CVH in adults with chronic diseases and healthy adults without chronic disease using the American Heart Association's (AHA's) Life's Essential 8 (LE8) metrics. Methods and Results We used National Health and Nutrition Examination Survey data from 2013 to 2018 to identify the presence of 16 chronic diseases by participant self‐report of diagnosis. We included adults aged 20 to 79 years. CVH was defined by AHA's LE8 metrics. Overall mean LE8 (range 0–100, higher = better CVH) and individual LE8 metric scores were calculated according to disease status for all participants and stratified by self‐identified sex, race, and ethnicity. There were 12 296 adults (51% women; mean age, 46 years) representing >186 million noninstitutionalized US adults. Significantly, and often substantially, lower CVH scores were noted for adults with chronic disease (14 of 16 diseases studied) versus unaffected adults, including all subtypes of cardiovascular disease, lung diseases, chronic kidney disease, liver conditions, cancer, arthritis, cognitive decline, and depression. For example, mean overall LE8 score was 14.0 points lower in those with versus without chronic obstructive pulmonary disease (51.0 versus 65.0, P<0.0001). Men and Black adults consistently had lower LE8 scores. Conclusions CVH is significantly poorer in adults with many chronic diseases compared with unaffected adults. These data suggest the utility of the LE8 score to identify groups for targeted optimization of CVH to enhance primary and secondary prevention efforts for cardiovascular disease and potentially for concomitant chronic diseases of aging.